ERROR ANALYSIS ON ENGLISH WRITING SKILL FOR THE FIRST SEMESTER STUDENTS - Bejo Sutrisno (Journal of English Language and Literature (JELL), 2016)
The objective of this research is to find out the most and the least of typical errors on the first semester students’ writing skill. Writing gives an important role to students in practicing their ability to express their ideas to readers. The students sometimes commit errors when they write and those errors can effect to the content of their writing, as the result, the readers will be confused or do not understand to the students’ writing. This research using content analysis method. The writer interprets the data based on the errors on the students’ writing. This research found that error analyzes of students’ writing on word form is in the first rank (14,6%) followed by word choice (11,5%), Article and add a word (9,5%), Omit a word, singular-plural, verb tense, and capitalization (8,3%), Word order and Incomplete sentence (6,2%) and the least error is on Meaning not clear, that is (0%). This research has the implication that the lecturers should treat errors made by students as a part of learning process and it should be solved through remedial activity.